Evaluating the potential of stabilised betacyanins from fermented red dragon fruit (Hylocereus polyrhizus) drink: sustainable colouration and antioxidant enhancement of stirred yoghurt - Lim, Teck Wei; Lim, Renee Lay Hong; Pui, Liew Phing; Tan, Chin Ping (Elsevier B.V., 2024)
Nowadays, the wide use of synthetic food colourant, Allura Red has elevated negative perceptions among consumers. As food industry players strive towards satisfying consumers’ demands, exploring new sustainable natural colourants with multifunctional properties (like betacyanins) has emerged as a novel concept. This study aimed to evaluate the potential of a functional fruit drink, Improved-FRDFD-dH2O [contained betacyanins of fermented red dragon fruit drink stabilised by 0.4 % xanthan gum and 0.5 % carboxymethyl cellulose hydrocolloid mixture solution and 0.2 % citric acid] to serve as a sustainable and stable functional liquid colourant in yoghurt. The 8-week refrigerated storage study revealed the betacyanins content in the yoghurt added with E162 experienced the lowest stabilities in terms of betacyanins content (>30 % degradation), viscosity (>15 % reduction), pH, LAB viability and antioxidant activity. In contrast, the Improved-FRDFD-dH2O was able to maintain the yoghurt's viscosity, syneresis, pH and LAB viability without any significant change. The betacyanins of Improved-FRDFD-dH2O had excellent stability in the yoghurt (<5 % degradation), showing only a minimal difference (ΔE<1.5) in total colour changes and being able to retain >86 % of the initial antioxidant activity by the end of storage. These findings support the Improved-FRDFD-dH2O as a sustainable functional colourant with antioxidant properties for producing beneficial yoghurt.